Associations between serum biomarkers and non-alcoholic liver disease: Results of a clinical study of Mediterranean patients with obesity - De Nucci, Sara; Castellana, Fabio; Zupo, Roberta; Lampignano, Luisa; Di Chito, Martina; Rinaldi, Roberta; Giannuzzi, Vito; Cozzolongo, Raffaele; Piazzolla, Giuseppina; Giannelli, Gianluigi; Sardone, Rodolfo; De Pergola, Giovanni (Frontiers in Nutrition, 2022)
Background Transient elastography is an ultrasound-based method to detect non-alcoholic fatty liver disease (NAFLD). Despite the simultaneously rising prevalence of fatty liver and metabolic disease, further information about metabolic risk indicators of fatty liver is still necessary. Methods A Southern Italian population sample with obesity (N = 87) was cross-sectionally explored for associations among the presence of NAFLD, assessed by FibroScan, and clinical, biochemical and anthropometric parameters. Inclusion criteria were age >18 years, BMI ≥ 25 kg/m2, no ongoing supplemental or drug therapy, including oral contraceptives or osteoporosis medications; exclusion criteria were pregnancy, endocrinological diseases, cardiovascular diseases, neoplasia, renal or hepatic failure, hereditary thrombocytopenia, hepatitis B (HBV) or hepatitis C virus (HCV) infection, and excess alcohol consumption. Results The study sample featured a female predominance (67%, N = 60), age range 18–64 years, and 40% prevalence of NAFLD, in accordance with the fibroscan-measured controlled attenuation parameter (CAP) threshold value above 302 dB/m. Males were slightly more frequently affected by NAFLD (51.4% vs. 48.6%, p = 0.01). Insulin levels, insulin resistance (quantified by HOMA-IR), diastolic blood pressure, BMI, visceral adipose tissue (VAT), and waist circumference were significantly higher in the NAFLD subset compared to their counterparts (p < 0.01, p < 0.01, p = 0.05, p < 0.01, p < 0.01, p < 0.01, respectively). Uric acid (p < 0.01) also showed a positive trend in the NAFLD group. Other liver steatosis parameters, measured by stiffness (p < 0.01), fatty liver index (FLI) (p < 0.01) and FibroScan-AST (FAST) (p < 0.01), were also significantly greater in the NAFLD group. In three nested linear regression models built to assess associations between CAP values and serum uric acid levels, a single unit increase in uricemia indicated a CAP increase by 14 dB/m, after adjusting for confounders (coefficient: 14.07, 95% CI 0.6–27.54). Conclusions Clinical-metabolic screening for NAFLD cannot ignore uricemia, especially in patients with obesity.